Case report: rTMS in combination with aripiprazole and sodium valproate for the maintenance treatment of rapid cycling bipolar disorder - Tao, Siyi; Chen, Bing; Xu, Xiaofang; Hu, Shaohua; Lu, Jing (Frontiers in Psychiatry, 2023)
As a safe neuromodulation therapy, rTMS is applied to treat a variety of psychiatric and neurological disorders. Additionally, both aripiprazole and sodium valproate are effective in the treatment of rapid cycling bipolar disorder. This case reports a female patient with a 17-year history of bipolar disorder who developed rapid-circulation bipolar disorder 5 years prior to presentation. After combined treatment with rTMS, aripiprazole, and sodium valproate, the patient’s mood remained stable and she was able to live and work normally.